2007
DOI: 10.1038/sj.bmt.1705663
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function in the acute course of allogeneic hematopoietic stem cell transplantation for hematological malignancies

Abstract: The aim of the study was to assess cognitive performance in patients with hematological malignancies before, and 3 months after, allogeneic hematopoietic stem cell transplant (HSCT). A consecutive sample of 39 patients was assessed before admission with a comprehensive neuropsychological test battery and health-related quality-oflife (HRQoL) questionnaires; 19 of these patients were retested around 100 days post HSCT. Test results were compared with normative data and revealed minimal differences at both time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 21 publications
(32 reference statements)
3
68
1
5
Order By: Relevance
“…It is plausible that had more comprehensive symptom measures been selected and applied in this population [60,[72][73][74] additional symptoms, than those reported in this study, may have emerged as prevalent. As a secondary analysis, this study was constrained by the use of an instrument that evaluates only two aspects of the symptom experience: symptom occurrence and symptom distress.…”
Section: Discussionmentioning
confidence: 76%
“…It is plausible that had more comprehensive symptom measures been selected and applied in this population [60,[72][73][74] additional symptoms, than those reported in this study, may have emerged as prevalent. As a secondary analysis, this study was constrained by the use of an instrument that evaluates only two aspects of the symptom experience: symptom occurrence and symptom distress.…”
Section: Discussionmentioning
confidence: 76%
“…Emotional functioning for survivors is most compromised before transplantation and immediately after, 23,24 with significant improvements seen as early as hospital discharge 23 to 100 days. 24,29,30 Some data suggest that emotional functioning remains relatively stable after this initial improvement, 23,29 although other data suggest that it continues to improve in the 2 24 to 4 26 years after transplantation. In general, survivors can expect average improvements in emotional functioning of .3 to .4 SD from before to after transplantation.…”
Section: Physical Functioningmentioning
confidence: 99%
“…2,23,24,27,29,30 Physical functioning then begins to improve, with 2 studies 2,24 finding that physical functioning plateaus in the year after transplantation and another study 26 finding continued improvement over 4 years. Regarding the magnitude of improvement, 3 studies reported that mean levels of posttransplantation physical functioning were higher by .1 to .2 SD compared with pretransplantation levels, 2,23,24 2 reported that they were lower by .8 to 1.3 SD, 29,30 and 2 did not report SD.…”
Section: Physical Functioningmentioning
confidence: 99%
“…Although chemotherapy induced damage of the white and grey matter of the brain has been reported to be causative, several publications connote that emotion and anxiety associated with the disease and it's treatment play a role [6,7,15].…”
Section: Resultsmentioning
confidence: 99%
“…Schultz-Kindermann et al, examined cognitive functioning before (n=39) and 3 months after (n=19) allogeneic transplantation for hematological malignancies [7]. They found that 26% of patients was impaired before as well as after transplant, but simple reaction time was significantly worse.…”
Section: Cognitive Impairment Associated With Hematopoietic Cell Tranmentioning
confidence: 99%